2016
DOI: 10.1103/physreva.93.066701
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Classical description ofH(1s)andH*(n=2)for cross-secti

Abstract: Cariatore et al. [Phys. Rev. A 91, 042709 (2015)] have introduced a modification of the classical trajectory Monte Carlo (CTMC) method, specially conceived to provide an accurate representation of charge-exchange processes between highly charged ions and H(1s), H * (n = 2). We point out that this new CTMC treatment is based on nonstable initial distributions for H * (n = 2) targets and an improper description of the H(1s) target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[32] is not stable and cannot be applied for excited states. The results of applying this distribution for collisions of multicharged ions with H(1s) have been compared with previous results in both the Comment [33] and the Reply [34], where it was found that at energies E ≈ 100 keV/u the distribution of Ref. [32] leads to EC partial cross sections practically identical to those calculated with the microcanonical distribution.…”
Section: Collisions Involving Bementioning
confidence: 81%
See 1 more Smart Citation
“…[32] is not stable and cannot be applied for excited states. The results of applying this distribution for collisions of multicharged ions with H(1s) have been compared with previous results in both the Comment [33] and the Reply [34], where it was found that at energies E ≈ 100 keV/u the distribution of Ref. [32] leads to EC partial cross sections practically identical to those calculated with the microcanonical distribution.…”
Section: Collisions Involving Bementioning
confidence: 81%
“…More recently, an alternative distribution has been proposed by Cariatore et al [32]. It has been shown [33] that the distribution of Ref. [32] is not stable and cannot be applied for excited states.…”
Section: Collisions Involving Bementioning
confidence: 99%
“…In their comment, Jorge et al [5] criticize our methodology along two main lines: (i) our initialization procedure for H * (n = 2), and (ii) they recall that the hydrogenic-Z-CTMC model is not physically correct even for H(1s) and should not be used at all. In what follows we will address these two issues.…”
mentioning
confidence: 99%